2022
DOI: 10.1136/jmedgenet-2022-108475
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic variants inWNT7Bdisrupt the development of multiple organs in humans

Abstract: BackgroundPulmonary hypoplasia, Diaphragmatic anomalies, Anophthalmia/microphthalmia and Cardiac defects delineate the PDAC syndrome. We aim to identify the cause of PDAC syndrome in patients who do not carry pathogenic variants inRARBandSTRA6, which have been previously associated with this disorder.MethodsWe sequenced the exome of patients with unexplained PDAC syndrome and performed functional validation of candidate variants.ResultsWe identified bi-allelic variants inWNT7Bin fetuses with PDAC syndrome from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…17,20,21 It is worth mentioning that we have previously shown that this role seems to be conserved in zebrafish where wnt7bb mutants display abnormal development of the swimbladder, the lung equivalent in zebrafish. 4 Abnormal tracheal development is another PDAC phenotype that is recapitulated in mice with WNT7B deficiency, which display incomplete cartilaginous rings. 21 Macrophage-induced apoptosis mediated by Wnt7b has been proposed as the mechanism for why Wnt7b deficient mice display pulmonary vascular defects and persistence of the hyaloid artery in the developing eye.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…17,20,21 It is worth mentioning that we have previously shown that this role seems to be conserved in zebrafish where wnt7bb mutants display abnormal development of the swimbladder, the lung equivalent in zebrafish. 4 Abnormal tracheal development is another PDAC phenotype that is recapitulated in mice with WNT7B deficiency, which display incomplete cartilaginous rings. 21 Macrophage-induced apoptosis mediated by Wnt7b has been proposed as the mechanism for why Wnt7b deficient mice display pulmonary vascular defects and persistence of the hyaloid artery in the developing eye.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the compelling human genetics data, WNT7B was an attractive candidate biologically. Indeed, we have shown that wnt7bb mutant zebrafish recapitulated a key phenotypic aspect of PDAC syndrome, that is, malformed swimbladder, the equivalent of lung hypoplasia in humans 4 . However, this association is not yet listed in OMIM pending independent confirmation and the current classification of the link between WNT7B and PDAC syndrome remains “Moderate” according to the ClinGen guidelines 5 .…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations